2015
DOI: 10.4236/mnsms.2015.51003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Verification of Resistance Spot Welding Results of Ultra-High Strength Steels through FE Simulations

Abstract: Resistance spot welding (RSW) is the most common welding method in automotive engineering due to its low cost and high ability of automation. However, physical weldability testing is costly, time consuming and dependent of supplies of material and equipment. Finite Element (FE) simulations have been utilized to understand, verify and optimize manufacturing processes more efficiently. The present work aims to verify the capability of FE models for the RSW process by comparing simulation results to physical expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…I NDUSTRY 4.0 refers to a series of profound changes towards high degree of inter-connectivity and smart manufacturing, involving large volume and variety of data in various industries [1], such as automotive, aerospace, manufacturing, etc. Resistance Spot Welding (RSW) is an automated manufacturing process widely applied for joining metal materials in these industries [2]. Worldwide RSW accounts for the production of over million of cars every year [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…I NDUSTRY 4.0 refers to a series of profound changes towards high degree of inter-connectivity and smart manufacturing, involving large volume and variety of data in various industries [1], such as automotive, aerospace, manufacturing, etc. Resistance Spot Welding (RSW) is an automated manufacturing process widely applied for joining metal materials in these industries [2]. Worldwide RSW accounts for the production of over million of cars every year [3].…”
Section: Introductionmentioning
confidence: 99%
“…To address the above issues, this paper presents a RSW ontology (RSWO) that is developed based on and assessed on the industrial scenario at Bosch. RSWO combines knowledge from three sources: knowledge acquired from experts working with Bosch; the concepts are aligned with ISO-14327 and ISO-14373 2 that is under practice in the Bosch welding 1 We briefly introduce ontology here and refer the readers to [4], [5]. In essence, an ontology is a formal specification of a domain of interest to describe a set of concepts (e.g., WeldingMachine, WeldingElectrode) and the relations between these concepts (e.g., etc ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many RSW studies showed that the formation of nuggets in any welded material depends on the optimized combination of parameters [4][5][6][7]. Weld quality is affected by several welding parameters: current intensity, welding time, force applied by the electrodes, contact resistance, and electrode size [8].…”
Section: Introductionmentioning
confidence: 99%
“…RSW is widely used for joining metallic materials in various industries due to its low cost and highly automated [7]. RSW uses the thermal effect of resistance generated by current flowing through the contact surface and adjacent areas of the workpieces to heat it to a molten or plastic state and then form a metal bond.…”
Section: Introductionmentioning
confidence: 99%